Globalisation: implications for health care delivery in developing countries - Louise de Villiers (AOSIS, 2005)
Globalisation entails a rapid increase in economic, technological and cultural exchange, which flows from economically and technologically dominant nations to less dominant nations. Opsomming Globalisering behels 'n toename in ekonomiese, tegnologiese en kulturele uitruiling vanaf ekonomies-dominante na ekonomies minder-dominante samelewings. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.